Impact of Biliary Atresia on Neurodevelopment in Children: A Systematic Review - Hisyam Hartaman Putra; Vanessa Permata Putri; Sri Wahyuni Evi Nafisyah; Mishbakhul Luthfi; Rahmat Hidayat Nur Ilhami; Siswanto Basuki (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Survival in children with biliary atresia (BA) has improved substantially, shifting clinical focus toward long-term morbidity, including neurodevelopmental outcomes. However, existing evidence remains fragmented, and prior reviews have not comprehensively addressed motor, behavioral, and autism-related domains. This study aimed to synthesize current evidence on neurodevelopmental outcomes in children with BA across cognitive, motor, and behavioral domains, and to identify clinical factors associated with adverse developmental trajectories. Methods: A systematic search of PubMed, Scopus, and Wiley was conducted from database inception to October 17, 2025, following PRISMA 2020 guidelines. Observational studies reporting neurodevelopmental outcomes in children (≤18 years) with BA were included. Risk of bias was assessed using the Newcastle–Ottawa Scale and the Joanna Briggs Institute checklist. Due to substantial heterogeneity, a narrative synthesis was performed. Result: Seven studies involving infants to adolescents with BA were included. Motor impairment was the most consistent finding, detectable from early infancy and persisting into later childhood. Cognitive outcomes were heterogeneous, ranging from significant impairment to age-appropriate or above-normative performance in selected cohorts. Behavioral and adaptive difficulties, including attention problems and autism spectrum–related traits, were frequently reported. Markers of disease severity such as unsuccessful Kasai portoenterostomy (KPE), delayed jaundice clearance, growth failure, ascites, and portal hypertension were consistently associated with poorer neurodevelopmental outcomes. Conclusion: Children with BA are at increased risk of multidimensional neurodevelopmental impairment, particularly affecting motor and behavioral domains. Early identification and longitudinal neurodevelopmental surveillance are essential to optimize long-term functional outcomes in this vulnerable population.